Recent advances in polyaniline-based micro-supercapacitors - Chu, Xiang (2023)
The rapid development of the Internet of Things (IoTs) and proliferation of wearable electronics have significantly stimulated the pursuit of distributed power supply systems that are small and light. Accordingly, micro-supercapacitors (MSCs) have recently attracted tremendous research interest due to their high power density, good energy density, long cycling life, and rapid charge/discharge rate delivered in a limited volume and area. As an emerging class of electrochemical energy storage devices, MSCs using polyaniline (PANI) electrodes are envisaged to bridge the gap between carbonaceous MSCs and micro-batteries, leading to a high power density together with improved energy density. However, despite the intensive development of PANI-based MSCs in the past few decades, a comprehensive review focusing on the chemical properties and synthesis of PANI, working mechanisms, design principles, and electrochemical performances of MSCs is lacking. Thus, herein, we summarize the recent advances in PANI-based MSCs using a wide range of electrode materials. Firstly, the fundamentals of MSCs are outlined including their working principle, device design, fabrication technology, and performance metrics. Then, the working principle and synthesis methods of PANI are discussed. Afterward, MSCs based on various PANI materials including pure PANI, PANI hydrogel, and PANI composites are discussed in detail. Lastly, concluding remarks and perspectives on their future development are presented. This review can present new ideas and give rise to new opportunities for the design of high-performance miniaturized PANI-based MSCs that underpin the sustainable prosperity of the approaching IoTs era.